The logic of acquiring practical knowledge and education - Helberg Chávez, Heinrich (2019)
In this article we try to reflect on the recently discovered logic of practical knowledge and its consequences for education and educational policies. This logic manifests itself in the process of socialization, which concatenates units of meaning that are social practices with implied and never formulated rules that require skills that the child acquires building its own universe of meaning. This is the frame of reference of the Young child: common sence and not his knowledge of the world, because his only source of knowledge is his language and his community. It is this process which evidences the real logic of language, because the way language is acquiered that is how it is. And only recognizing the dominant place that the logic of the practical knowledge has, is that we can lay the groundwork for a pertinent and intercultural education that can avoid the problems of cultural rejection that always face the educational projects that are not based on the educational cultures of peoples.